2015
DOI: 10.1037/adb0000067
|View full text |Cite
|
Sign up to set email alerts
|

Social processes explaining the benefits of Al-Anon participation.

Abstract: This study examined social processes of support, goal direction, provision of role models, and involvement in rewarding activities to explain benefits of participating in Al-Anon, a 12-step mutual-help program for people concerned about another person’s substance use. Newcomers to Al-Anon were studied at baseline and 6 months later, when they were identified as having sustained attendance or dropped out. Among newcomers, and among established Al-Anon members (“oldtimers”), we also used number of Al-Anon meetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 46 publications
0
4
0
3
Order By: Relevance
“…Por outro lado, o modelo de codependência praticado e amplamente difundido pelos grupos de mútua ajuda destinados a acolher familiares de dependentes químicos, como, por exemplo, o Al-Anon, Nar-Anon e o Alateen, tem se mostrado uma ferramenta importante [21][22][23][24] , que promove segurança, estabilidade e esperança às famílias cujos membros são portadores da síndrome de dependência ao álcool. Além disso, tende a fornecer suporte social e eficácia no potencial para mudar o comportamento do bebedor e do uso de drogas [25][26][27][28][29] . Portanto, justifica-se a importância de conduzir uma revisão da literatura na tentativa de verificar qual é o estado da arte tanto do conceito quanto da etiologia e de outros fatores relacionados ao constructo codependência entre familiares de usuários de álcool e outras drogas, sendo este o objetivo deste estudo.…”
Section: Introductionunclassified
“…Por outro lado, o modelo de codependência praticado e amplamente difundido pelos grupos de mútua ajuda destinados a acolher familiares de dependentes químicos, como, por exemplo, o Al-Anon, Nar-Anon e o Alateen, tem se mostrado uma ferramenta importante [21][22][23][24] , que promove segurança, estabilidade e esperança às famílias cujos membros são portadores da síndrome de dependência ao álcool. Além disso, tende a fornecer suporte social e eficácia no potencial para mudar o comportamento do bebedor e do uso de drogas [25][26][27][28][29] . Portanto, justifica-se a importância de conduzir uma revisão da literatura na tentativa de verificar qual é o estado da arte tanto do conceito quanto da etiologia e de outros fatores relacionados ao constructo codependência entre familiares de usuários de álcool e outras drogas, sendo este o objetivo deste estudo.…”
Section: Introductionunclassified
“…Adult offspring often referred to a lack of communication in their families growing up and the awkward silences that existed surrounding the parent with harmful drinking. Perhaps the online forum is seen more as an outlet for expressing their own voice rather than responding to the needs of others, similar to that of 12-Step groups, where sharing one’s story is an important component of recovery (Timko, Halvorson, Kong, & Moos, 2015). These supportive messages involving identification seem to take the focus off the other person and back to the individual.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that despite parents’ desire to assist their child in recovery, they often underestimate or do not understand their role in treatment (Gogel et al, 2011; Groenewald & Bhana, 2016). Various organized peer groups, such as Al-Anon, provide emotional and social support for parents of individuals with SUD through bonding, goal direction, and mentorship (Timko et al, 2015). However, no one story of parenting a loved one in SUD recovery is the same as each familial unit has specific concerns regarding family dynamics, economic considerations, and level of parental involvement.…”
Section: Literature Reviewmentioning
confidence: 99%